Atividade física regular orientada e saúde mental em estudantes e profissionais da área da saúde em tempos de pandemia de COVID-19 - Gomes, André Luiz Guimarães (2022)
The World Health Organization declared the new coronavirus SARS-CoV-2 (COVID-19) as a pandemic on March 11, 2020. Restrictive measures were adopted in an attempt to contain the virus, however they caused negative impacts on people's emotional aspect. If no specific care intervention is carried out, it is estimated that between one-third and one-half of the population will suffer some type of psychopathological manifestation. Students in the health areas are more vulnerable to the development of psychopathological problems, due to the great exposure to stressors, so the current moment can aggravate this vulnerability. Healthcare professionals are particularly vulnerable to suffering from mental illness due to the nature of their work, which is often stressful, with irregular shifts and working hours and a high-pressure environment. In a pandemic situation, the class has a greater predisposition to even more serious psychic complications, especially among those who work on the "front line". It is known that physical activity has positive relationships with physical and mental well-being and quality of life. The objective of the present study is to characterize the physical activity of students and health professionals before and during the Covid-19 pandemic and to investigate the relationships between levels of physical activity and well-being during the pandemic. Quantitative, descriptive, correlational and cross-sectional study, carried out among students and professionals in the health areas, during the period of the Covid-19 pandemic, in 2020. The researcher invited to participate in the research, initially those from the personal and professional circle of the same, and which was expanded using the strategy of xvii snowball sampling. The study sample consisted of 305 participants, of which 159 (52.1%) were students and 146 (47.9%) were health professionals. Students and health professionals, for the most part, were practicing AFO during the pandemic, with a higher rate for those who already practiced it before, are mostly satisfied with their QOL, and report satisfaction with their health, mostly among the students. professionals and, to a lesser extent, among students. The QOL assessment shows the best results in the environment domain. The practice of AFO in the pandemic improves QOL in at least one domain among students and even all domains among professionals. High levels of R in the 2 categories, with no differences between the 4 groups, in any of the categories. Most of the sample does not have MMD, with a greater predominance in the professional category, with no significant differences in the total score between the 4 groups, but with a smaller reduction in vital energy associated with AFO at the time of the pandemic for students. Conclusion: These results emphasize a relationship, but not an implicit causality, between AFO and general mental health, since, as a cross-sectional study, cause and effect cannot be implied between the variables. The mental health benefits related to AFO are evident in the sample of this study.